Academic Burnout and Its Relationship with Employment Hope among Health Sciences Students - Hamed Aghaei; Taleb Askaripoor; Ayat Rahmani; Vahideh Abolhasannejad; Masoud Shafii motlagh; Ali Mohammad Abbasi; Mohammad Ebrahim Ghaffar; Elahe Kazemi (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: The study of academic burnout and its predictors as one of the main challenges of the educational system is of great importance. This research was conducted to investigate and explain the role of hope for employment and its subscales in predicting academic burnout. Materials & Methods: All health sciences students at Ilam, Arak, Birjand, Semnan, and Hamedan Universities of Medical Sciences, Iran, in 2019 were examined in this descriptive-correlation study. The samples were selected using a stratified random sampling method (n=400). The required data were gathered using the Academic Burnout Questionnaire (developed by Berso et al.) and the Qureshi Rad Employment Hope Questionnaire. The collected data were analyzed in the SPSS-20 software using an independent t-test, one-way ANOVA, and simple and multiple linear regressions. Results: The results of the study showed that 2.3%, 61.3%, and 36.5% of students suffered from low, medium, and high levels of academic burnout, respectively. The mean ± SD of the hope for employment score was 55.69±14.61, indicating a moderate level of hope for employment among the study participants. Based on the study results, 8.4% of the variance of academic burnout could be predicted by hope for employment (F=37.58, R=0.298, R2=0.086, adjusted R2=0.084, P<0.001). Conclusion: The study findings revealed the positive effect of hope for employment on academic burnout. In addition to reducing academic burnout, interventions focused on increasing employment hope can also improve the academic performance of health sciences students.